Reforms and Infrastructure Efficiency in Spain’s Container Ports - González, María Manuela; Trujillo, Lourdes (World Bank, Washington, DC, 2012)
This paper quantifies the evolution of technical efficiency in port infrastructure service provision in the major Spanish port authorities involved in container traffic. The paper also analyzes the extent to which port reforms that took place in the 1990's had an impact on the efficiency of the Spanish container ports. Because of the multi-output nature of port activities, we have estimated a distance function, which is a novel methodology in the study of the port industry. The results show that the reforms resulted in significant improvements in technological change, but that technical efficiency has in fact changed little on average. However, there is a significant movement of the efficiency within ports over time as a result of these reforms.